PENYELESAIAN KLAIM ASURANSI KAPAL BERBENDERA INDONESIA TERHADAP PERJANJIAN ASURANSI YANG DISEPAKTI TUNDUK PADA HUKUM INGGRIS BERDASARKAN PENGADILAN INDONESIA - Tazani, Afdolludin Afta; Utomo, Agus Prabowo Dany; Putra, Vika Achmad Danny Angga (UNIMAR AMNI Semarang, 2024)
Risks that often occur in ship shipping can occur due to human error factors, technical factors or natural factors (force majeure factors) and other factors. The large number of accidents or incidents that frequently occur can cause a lot of loss and damage and even loss for the owner of the ship and third parties as owners of the goods. As in the case that occurred at PT. AHAP and PT. PM . PT insurance dispute. AHAP and PT.PM occurred because the ship from PT. Which PM is KM. Bayu Prima experienced a fire.This writing aims to describe the process of resolving disputes over Indonesian ship insurance agreements using English law in the Indonesian Courts and to find out the obstacles faced by Indonesian Courts in resolving insurance disputes whose insurance agreements use English law. The method used is the Normative Juridical research type. This type of Normative Juridical research aims to examine statutory regulations related to theoretical concepts. Settlement of disputes over Indonesian Ship InsuranceAgreements Using English Law in Indonesian Courts is very difficult to use because insurance policies use English law, so Indonesian courts do not have the right to decide on sanctions based on the insurance policy in force. The obstacle faced by Indonesian courts in resolving insurance disputes where the insurance agreement uses English law is the use of insurance policy agreements that use English law. Withthe insurance policy agreement using English law, the Indonesian Court does not have full authority to decide disputes, thereby causing harm to PT. AHAP who cannot claim applicable damages.